Strategy-Oriented Exact Pattern Grouping Approaches for Integrated Circuit Designs - Gan, Yuan; Ding, Ming; Han, Chunying; Yan, Changlian; Jiang, Junhai; Zhang, Rongjia; Yu, Zongqiang (2022 International Workshop on Advanced Patterning Solutions (IWAPS), 2022)
Exact layout pattern grouping has been utilized in recent years in integrated circuit design for manufacturability (DFM) applications. In this paper, we have developed several approaches of exact layout pattern grouping for different purposes. For achieving a small cluster count and largest repeating patterns, we have developed greedy mode and rich mode; For selecting layout patterns in non-period regions, orphan strategy is adopted. Moreover, clip shifting is supported in all grouping modes above, which reduces the cluster count effectively and efficiently. The performances of the developed algorithms are validated by numerical experiments on a full-chip layout GDSII file containing millions of polygons.